Vaccine Response in Patients With Multiple Sclerosis Receiving Teriflunomide - Tornatore, Carlo; Wiendl, Heinz; Lublin, Alex L.; Geertsen, Svend S.; Chavin, Jeffrey; Truffinet, Philippe; Bar-Or, Amit (Frontiers in Neurology, 2022)
Many patients with multiple sclerosis (MS) receive disease-modifying therapies (DMTs), such as teriflunomide, to reduce disease activity and slow progression. DMTs mediate their efficacy by modulating or suppressing the immune system, which might affect a patient’s response to vaccination. As vaccines against the SARS-CoV-2 virus become available, questions have arisen around their efficacy and safety for patients with MS who are receiving DMTs. Data are beginning to emerge regarding the potential influence of certain DMTs on a patient’s response to coronavirus disease 2019 (COVID-19) vaccines and are supported by evidence from vaccination studies of other pathogens. This review summarizes the available data on the response to vaccines in patients with MS who are receiving DMTs, with a focus on teriflunomide. It also provides an overview of the leading COVID-19 vaccines and current guidance around COVID-19 vaccination for patients with MS. Though few vaccination studies have been done for this patient population, teriflunomide appears to have minimal influence on the response to seasonal influenza vaccine. The evidence for other DMTs (eg, fingolimod, glatiramer acetate) is less consistent: some studies suggest no effect of DMTs on vaccine response, whereas others show reduced vaccine efficacy. No unexpected safety signals have emerged in any vaccine study. Current guidance for patients with MS is to continue DMTs during COVID-19 vaccination, though adjusted timing of dosing for some DMTs may improve the vaccine response.